2023
DOI: 10.1111/jvim.16891
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of pimobendan after oral administration to dogs with myxomatous mitral valve disease

Anna K. McManamey,
Teresa C. DeFrancesco,
Kathryn M. Meurs
et al.

Abstract: BackgroundPimobendan is an important therapy for dogs with myxomatous mitral valve disease (MMVD). The pharmacokinetics are reported in healthy dogs but not in dogs with heart disease.Hypothesis/ObjectivesTo determine if dog characteristics such as age, breed, body condition score, ACVIM stage of heart disease or biochemical laboratory value alter the pharmacokinetics of orally administered pimobendan and its metabolite in a cohort of dogs with naturally occurring MMVD.AnimalsFifty‐seven client‐owned dogs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
2
0
0
Order By: Relevance
“…Of these parameters, ESVI, LVIDSN, FS, EF, and E wave remained statistically unchanged from the Compared to the values of the Control group at the same timepoint, the PIMO PO group showed significant differences in FS and EF at T30, and in CI, ESVI, LVIDSN, FS, EF, LA/Ao, IVCT, and LVET at T60. This suggests that the effect of oral pimobendan was enhanced up to 90 min after administration, which is consistent with previous studies on the pharmacokinetics of oral pimobendan (34,35). In one study, maximal cardiovascular effects were observed 2-4 h after a single oral dose (0.26-0.28 mg/kg) in healthy dogs (35) whereas, in another study, the mean time to peak concentration with a single oral dose of pimobendan in dogs with MMVD was 1.66 h, independent of the ACVIM stage (34).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of these parameters, ESVI, LVIDSN, FS, EF, and E wave remained statistically unchanged from the Compared to the values of the Control group at the same timepoint, the PIMO PO group showed significant differences in FS and EF at T30, and in CI, ESVI, LVIDSN, FS, EF, LA/Ao, IVCT, and LVET at T60. This suggests that the effect of oral pimobendan was enhanced up to 90 min after administration, which is consistent with previous studies on the pharmacokinetics of oral pimobendan (34,35). In one study, maximal cardiovascular effects were observed 2-4 h after a single oral dose (0.26-0.28 mg/kg) in healthy dogs (35) whereas, in another study, the mean time to peak concentration with a single oral dose of pimobendan in dogs with MMVD was 1.66 h, independent of the ACVIM stage (34).…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that the effect of oral pimobendan was enhanced up to 90 min after administration, which is consistent with previous studies on the pharmacokinetics of oral pimobendan (34,35). In one study, maximal cardiovascular effects were observed 2-4 h after a single oral dose (0.26-0.28 mg/kg) in healthy dogs (35) whereas, in another study, the mean time to peak concentration with a single oral dose of pimobendan in dogs with MMVD was 1.66 h, independent of the ACVIM stage (34).…”
Section: Discussionsupporting
confidence: 92%